DERAJAT KEASAMAN DAN ANGKA REDUKTASE SUSU KAMBING PERANAKAN ETTAWA PASTEURISASI DENGAN LAMA SIMPAN YANG BERBEDA PADA SUHU REFRIGERATOR 4℃ - Egil Olsen; Arif Qisthon; Veronica Wanniatie; Ali Husni (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2021)
This study aimed to determine the effect of storage time at 4℃ refrigerator temperature on degrees of acidity and reductase score in pasteurized Ettawa goat milk and to determine the optimum storage time for pasteurized goat milk. This research was conducted in March–April 2020, at the Livestock Production Laboratory, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. The research material used was 6 liters of Ettawa Grade goat milk. This study used a completely randomized design, with 5 treatments and 4 replications, namely Pasteurized goat's milk stored for 0 days (P0), Pasteurized goat's milk was stored for 6 days (P1), Pasteurized goat's milk stored for 12 days (P2), Pasteurized goat's milk stored for 18 days (P3), and pasteurized goat milk stored for 24 days (P4). The variables observed were the degree of acidity, the amount of reductase, and the optimum storage time. The data obtained were then analyzed for variance / Analysis of Variance (ANOVA) at the 5% significance level and continued with the Least Significant Difference (LSD) test. The results showed that pasteurized Ettawa goat's milk with a storage time of 24 days at 4℃ refrigerator temperature had no significant effect on the degrees of acidity, but had a significant effect on the methylene blue reductase test. The conclusion of this research is that the storage time of Pasteurized goat's milk for 12 days at 4℃ temperature is the optimum storage time to maintain the quality of milk with degrees of acidity of 7.5°SH and a reductase score for 8 hours. Keywords: Reductase number, Titratable acidity, Pasteurization, Refrigerator, Goat milk